Education and within groups earning inequality in Pakistan - Maqbool H. Sial; Ghulam Sarwar; Waseem Akram (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2018)
The present study focuses on identifying and estimating the extent of earning inequality due to increase in the level of education in Pakistan. Utilizing four rounds of household level surveys conducted at national level during 2001-2014, the study analyzes the effect of education on earning inequality within workers having same level of education. Quantile regression is employed to estimate and test earning inequality within workers having primary, secondary and tertiary education respectively. The results confirm that there is significant heterogeneity in the returns within each level of education. Such disparities are shown to be larger for workers at upper quantiles of the earnings distribution versus the lower counterpart. The results also show that within-group earning inequality is higher for workers with tertiary education than with secondary and primary education. Finally, the findings suggest that earning inequality does not remain same over time. These dynamic changes have enlarged lower as well as upper tail of earning distribution causing further income inequality in Pakistan. Therefore, these findings has identified that heterogeneity in the returns has very serious implication for distribution of income, general welfare and labor markets in Pakistan.
Keywords: 330; human capital; education; earnings distribution; quantile regression